Carbohydrate mouth rinse does not affect performance during a 60-min running race in women - Chryssanthopoulos, C.; Ziaras, C.; Oosthuyse, T.; Lambropoulos, I.; Giorgios P, P.; Zacharogiannis, E.; Philippou, A.; Maridaki, M. (Journal of Sports Sciences, 2018)
This study examined the effect of carbohydrate mouth rinsing on endurance running performance in women. Fifteen female recreational endurance runners, who used no oral contraceptives, ran two races of 1-h duration on an indoor track (216-m length) at 18:00 h after an 8-h fast with a 7-days interval between races, corresponding to the 3rd-10th day of each premenopausal runner`s menstrual cycle, or any day for the postmenopausal runners. In a double-blind random order, participants rinsed their mouth with 25 ml of either a 6.4% carbohydrate (RCHO) or a placebo solution (RP). No fluid was ingested during exercise. Serum 17ß-?stradiol (P = 0.59) and Progesterone (P = 0.35) did not differ between treatments. There was no difference in 1-hour running performance (RCHO: 10,621.88 ± 205.98 m vs. RP: 10,454.00 ± 206.64 m; t = 1.784, P = 0.096). Furthermore, the mean percentage effect (±99%CI) of RCHO relative to RP, 1.67% (-1.1% to 4.4%), and Cohen`s effect size (d = 0.21) support a trivial outcome of RCHO for total distance covered. In conclusion, carbohydrate mouth rinsing did not improve 60-min track running performance in female recreational runners competing in a low ovarian hormone condition, after an 8-h fast and when no fluid was ingested during exercise.